TATA KELOLA PEMERINTAH DESA DALAM PEMANFAATAN LAHAN PEKARANGAN UNTUK KESEJAHTERAAN EKONOMI KELUARGA DI DESA SIPODECENG - Rukmini Rukmini; Muhammad Rais Rahmat Razak; Sandi Lubis; Yayuk Astuti; Mutiah Khaerunnisa (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2026)
This study aims to analyze village government governance in the utilization of yard land and identify the challenges faced in supporting family economic welfare in Sipodeceng Village, Baranti District, Sidenreng Rappang Regency. The utilization of yard land is one of the strategies used by rural communities to improve food security and household income, thus requiring good and participatory governance from the village government. This study uses a qualitative approach with a case study method. Data were collected through in-depth interviews, observations, and document analysis, then analyzed thematically with the help of NVivo software to map patterns of field findings. The results show that the governance of the Sipodeceng Village Government in the utilization of yard land has implemented most of the principles of Good Governance, including participation, transparency, accountability, effectiveness-efficiency, and the rule of law. The community is actively involved in the planning and implementation of programs, while the village government strives to convey information openly and be accountable for the implementation of activities. However, the implementation of this governance still faces several challenges, such as limited time and knowledge of the community, unequal distribution of information, limited technical assistance and agricultural facilities, and the absence of specific regulations related to the utilization of yard land. This study concludes that good village government governance plays an important role in encouraging the utilization of yard land as a source of income and economic security for families. Despite various obstacles, the practice of utilizing backyard land has had a positive impact on reducing expenses, increasing additional income, and strengthening family food security. This study provides theoretical implications for the development of governance and village development science, practical implications for the community in managing backyards productively, and policy implications for village and local governments in formulating more effective and sustainable empowerment programs.